2019
DOI: 10.1111/nhs.12637
|View full text |Cite
|
Sign up to set email alerts
|

Recovery college as a transition space in the journey towards recovery: An Australian qualitative study

Abstract: Recovery colleges are formal learning programs that aim to support people with a lived experience of mental illness. In this study, we aimed to explore the experiences of participants in a pilot recovery college that opened in Adelaide, South Australia, in 2016. A qualitative exploratory study was conducted involving interviews with learners (n = 8) and focus groups with lived experience facilitators (course facilitators with a lived experience of mental illness, n = 5), Clinician facilitators (mental health s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
(33 reference statements)
2
5
0
Order By: Relevance
“…Overall, the preliminary findings indicated that recovery college in postsecondary setting benefitted students through knowledge acquisition, improved mental health and wellbeing, and mental health service utilization. These findings are in keeping with existing studies that identify the effectiveness of recovery colleges in community settings (Bourne et al, 2018; Ebrahim et al, 2018; Kay & Edgley, 2019; Muir-Cochrane et al, 2019). Hopkins, and colleagues (2018) demonstrated promising results of a youth based recovery college in Australia, but the college did not include postsecondary students.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Overall, the preliminary findings indicated that recovery college in postsecondary setting benefitted students through knowledge acquisition, improved mental health and wellbeing, and mental health service utilization. These findings are in keeping with existing studies that identify the effectiveness of recovery colleges in community settings (Bourne et al, 2018; Ebrahim et al, 2018; Kay & Edgley, 2019; Muir-Cochrane et al, 2019). Hopkins, and colleagues (2018) demonstrated promising results of a youth based recovery college in Australia, but the college did not include postsecondary students.…”
Section: Discussionsupporting
confidence: 87%
“…Many of the recovery colleges in North America and Europe are situated within mental health community services (Whitley et al, 2019) and were initially offered in person, in classrooms within the centers. The considerable amount of evidence on the efficacy of recovery colleges in mental health contexts (Bourne et al, 2018; Muir-Cochrane et al, 2019; Sommer et al, 2019; Toney et al, 2018; Wilson et al, 2019) has led to an exploration of their implementation in novel settings in Canada (i.e. those not embedded into mental health services and those devoted to special populations) – specifically, within the post-secondary school context.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence for recovery-oriented models in improving the wellbeing of people with SMI [ 53 , 54 ]. Leamy’s personal recovery framework CHIME (Connectedness, Hope and optimism, Identity, Meaning, Empowerment) is one such model [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Personal recovery is another crucial arm of this proposed new framework. There is no doubt that the elements of CHIME [ 55 ] and other recovery models [ 54 ] play significant roles in motivating a person with SMI to initiate self-management and self-care. The same reasons also help sustain improved health behaviours in people with SMI.…”
Section: Discussionmentioning
confidence: 99%
“…At the heart of the recovery college model is a learning approach in which the process of co-production equalises the traditional power relationships in mental health services, bringing people from all walks of life together, as both students and experts. Recovery colleges link mental health recovery approaches with pedagogical principles (Muir-Cochrane et al, 2019). The colleges aim to assist participants to identify and achieve personal learning goals and to develop their own personal skills and knowledge.…”
Section: Introductionmentioning
confidence: 99%